Secondary glaucoma in CAPN5-associated neovascular inflammatory vitreoretinopathy - Cham A; Bansal M; Banda HK; Kwon Y; Tlucek PS; Bassuk AG; Tsang SH; Sobol WM; Folk JC; Yeh S; Mahajan VB (Clinical Ophthalmology, 2016)
Abdourahman Cham,1,2 Mayank Bansal,3 Himanshu K Banda,4 Young Kwon,1 Paul S Tlucek,1 Alexander G Bassuk,5 Stephen H Tsang,6,7 Warren M Sobol,8 James C Folk,1 Steven Yeh,4 Vinit B Mahajan1,2 1Department of Ophthalmology and Visual Sciences, 2Omics Laboratory, University of Iowa, Iowa City, IA, USA; 3Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, India; 4Department of Ophthalmology, Emory University School of Medicine, Atlanta, GA, 5Department of Pediatrics, University of Iowa, Iowa City, IA, 6Barbara and Donald Jonas Laboratory of Stem Cells and Regenerative Medicine and Bernard and Shirlee Brown Glaucoma Laboratory, Department of Pathology and Cell Biology, Institute of Human Nutrition, College of Physicians and Surgeons, Columbia University, 7Edward S Harkness Eye Institute, New York-Presbyterian Hospital, New York, NY, 8Retina Physicians & Surgeons, Inc., Dayton, OH, USA Objective: The objective of this study was to review the treatment outcomes of patients with secondary glaucoma in cases of autosomal dominant neovascular inflammatory vitreoretinopathy (ADNIV), a hereditary autoimmune uveitis due to mutations in CAPN5. Patients and methods: A retrospective, observational case series was assembled from ADNIV patients with secondary glaucoma. The main outcome measures were intraocular pressure (IOP), visual acuity, use of antiglaucoma medications, ocular surgeries, and adverse outcomes. Perimetry and optic disk optical coherence tomography (OCT) were also analyzed. Results: Nine eyes of five ADNIV patients with secondary glaucoma were reviewed. Each received a fluocinolone acetonide (FA) implant for the management of posterior uveitis. Following implantation, no eyes developed neovascular glaucoma. Five eyes (in patients 1, 2, and 5) required Ahmed glaucoma valve surgery for the management of steroid-responsive glaucoma. Patient 2 also developed angle closure with iris bombe and underwent laser peripheral iridotomy. Patient 4 had both hypotony and elevated IOP that required periodic antiglaucoma medication in the FA-implanted eye. Patient 3 did not develop steroid-response glaucoma in either eye. Optic disk examinations were obscured by fibrosis and better assessed with OCT. Conclusion: ADNIV patients show combined mechanism secondary glaucoma best assessed by OCT of the optic disk. The FA implants have reduced uveitic and neovascular glaucoma. Nevertheless, IOP management remains complex due to steroid-response glaucoma, angle closure glaucoma, and hypotony. Keywords: ADNIV, CAPN5, calpain-5, fluocinolone acetonide, secondary glaucoma, uveitis